Biophysics an introduction - Cotterill, Rodney M. J. (Chichester John Wiley, 2003)
This is a concise balanced introductin to this subject. Written in an accessible and readable style, the book takes a fresh, modern approach with the author successfully combining key concepts and theory with relevant applications and examples drawn from the field as a whole. * A carefully structured introduction to biophysics and medical physics * Combines coverage of the basic concepts and ideas along with the more cutting edge developments * Assumes little biological or medical knowledge * Includes a supplementary website which will include animations, simulations, colour images, additional content, solutions and links to other sites
Keywords: Biophysics